The discovered book Das Hauß=Ʒucht= und Lehr=Buch Jeſu Syrachs (1671) by Georg Mancelius and relations with its earlier publications - Kazakėnaitė, Ernesta (Baltistica, 2020)
This article consists of two following parts: presentation of discovered book (section 2) and its analysis (section 3, 4 and 5). The third edition of the Book of Sirach by Mancelius published in 1671 was up to this day considered not to be extant but it was found in very good state stored in the Lund University Library (call number: lub.1356710). The discovery of the book made it possible to compare it with the previous ones and to examine the statement that it differed very little from the others, mostly in spelling. The comparison of the Sir3 text with its earlier editions disclosed a relatively high number of various linguistic differences, differences in the verse structure and other peculiarities. The scope of this article only allowed to examine the following text modifications (44 cases): additions (35), omissions (6) and verse distribution (3). The largest number of the changes was identified in the first part of the translation, especially towards the middle of the text. A common trend that emerged in examining the changes was that they occurred as a result of a more conservative approach of the editors which manifested in the attempts to bring the translated text closer to Luthers Bible having chosen the strategy of more literal (word-for-word) translation. In order to determine the motivation of the changes, the article has also attempted at exploring the issue of the source of the translation. Analysis seems to suggest that the main source of the translation of Sir by Mancelius was the German text by Luther but it is also obvious that other texts were used as translation ancillary sources too.
Keywords: Latvian; 17th century; Georg Mancelius; the Book of Sirach; 3rd edition; additions; omissions